Determinação de zonas de manejo para adubação nitrogenada em lavoura de tomate industrial - (:unkn) unknown (Universidade Estadual de Goiás, 2011)
The tomato crop production in Brazil is concentrated in the Southeast and Midwest, and Goias stands out as the largest domestic producer, primarily of processing tomatoes. The strong growth in production and productivity of tomato in Goiás is directly related to the expansion of that product processing industry in the state. The crop of processing tomatoes is very demanding in nitrogen and periodic assessment of the nutritional status of tomato can help in fertilization practices, since studies show that concentrations of chlorophyll are directly linked to levels of N in the soil. This study aimed to define management zones for nitrogen fertilization on crop processing tomato based on spatial variability of leaf SPAD index obtained by portable meters. The experiment was conducted in an area cultivated with tomato industrial and irrigated by center pivot, in the municipality of Morrinhos (GO). Data were collected in an area of 23 ha and a sampling grid with spacing of 50x50 m, totaling 120 sampling points, which were georeferenced. The variables analyzed for each sample point were: pH, K, P, Ca, Mg, Al, Zn, H + Al, MO, CTC, V%, SPAD index (obtained from portable meter), foliar N, foliar K and foliar P, total yield, number of green tomatoes, good and spoiled. Data were analyzed descriptively and to characterize the spatial variability using geostatistical methods by setting up models of semivariograms for lowest sum of squared residues (SSR) and higher coefficient of determination (R2). Checked the spatial dependence through kriging were prepared thematic maps. For delineation of management zones from the interpolated maps of variability we used the K-means algorithm Fuzzi and to define the optimal number of classes was determined Fuzzi performance index and the modified partition entropy. The variables used for defining management zones were SPAD indices 1 (leaf reading at 43 days after transplantation) and SPAD index 4 (leaf reading at 58 days after transplantation). From these variables were generated maps management zones and for each variable involved in the study area was divided into two, three, four and five classes. Later the Kappa test was analyzed the correlation between the maps generated by management zones and maps of the levels of N, P and K obtained from the leaf analysis laboratory. Considering two management zones, the overall hit rate obtained from the SPAD with the classes obtained maps of foliar N was approximately 51% and approximately 37% when considered three management zones. The results allowed the classification set two three management zones, which had an average value for the first SPAD index of 58.9 and 56.2 for the management zones one and two, respectively, and 57.2, 59, 2 and 55.5 for the management zones one, two and three respectively. There were significant differences (p ≤ 0.05) between management zones obtained from the SPAD index, average indices for SPAD and also to the average productivity of industrial tomatoes. It was found that the SPAD index obtained by means of meters foliar is a portable instrument that allows a rapid leaf need for nitrogen by plants and the possibility of localized application of this nutrient in crop processing tomatoes.
Keywords: Geoestatística; Agricultura de precisão; Teste de kappa; Algoritmo fuzzi k-means; Geostatistics; Precision Agriculture; Kappa test; Fuzzy k-means algorithm; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA